Komparace vybraných finančních ukazatelů českých bank a jejich zahraničních vlastníků - Černohorská, Liběna; Černohorský, Jan (Univerzita Pardubice, 2007)
The paper deals with the analysis and examination of the financial situation development of monitored bank institutions operating in the Czech Republic in the comparison with thein foreign holders according to the chosen financial indicators.
Keywords: bank; Financial analysis; comparison